2020
DOI: 10.1186/s12860-020-00287-w
|View full text |Cite
|
Sign up to set email alerts
|

The local hypothalamic–pituitary–adrenal axis in cultured human dermal papilla cells

Abstract: Background Stress is an important cause of skin disease, including hair loss. The hormonal response to stress is due to the HPA axis, which comprises hormones such as corticotropin releasing factor (CRF), adrenocorticotropic hormone (ACTH), and cortisol. Many reports have shown that CRF, a crucial stress hormone, inhibits hair growth and induces hair loss. However, the underlying mechanisms are still unclear. The aim of this study was to examine the effect of CRF on human dermal papilla cells (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…69 The results may also suggest that a fully functional HPA axis exists in human DPCs and that CRF directly affects human DPCs, as well as human HFs, under conditions of stress. 69 Androgenetic alopecia (AGA) is thought to be aggravated by stress too. 70 CRF was used to induce a stress response in human ex vivo male AGA HFs.…”
Section: Acne the Hpa Axis And Psychodermatologymentioning
confidence: 88%
See 1 more Smart Citation
“…69 The results may also suggest that a fully functional HPA axis exists in human DPCs and that CRF directly affects human DPCs, as well as human HFs, under conditions of stress. 69 Androgenetic alopecia (AGA) is thought to be aggravated by stress too. 70 CRF was used to induce a stress response in human ex vivo male AGA HFs.…”
Section: Acne the Hpa Axis And Psychodermatologymentioning
confidence: 88%
“…Several reports have shown that CRF inhibits hair growth and induces hair loss 69 . However, the underlying mechanisms are still ambiguous 69 .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that prolonged stress can increase inflammatory cytokines (e.g.INF-ɣ) leading to inflammation and ending up in apoptosis, cell senescence and premature catagen transition. DPCs in hair follicle possess receptors for corticotropin releasing factor (CRF) [ 18 ]. When the individual is under stressful events, production of CRF in hypothalamus increases.…”
Section: Alopecia and Its Classificationmentioning
confidence: 99%
“…In addition, it accounts for the accumulation of reactive oxygen species (ROS) which also stop the cell cycle. CRF downregulate the expression levels of anagen-related cytokines such as hepatocyte growth factor (HGF), Wnt5a, TGFβ, Vascular endothelial growth factor (VEGF) and versican [ 18 ]. Stress resulting from hair loss contributes to a negative feedback elevating hair loss incidence [ 19 ].…”
Section: Alopecia and Its Classificationmentioning
confidence: 99%
“…CRH also exerts multiple other functions, such as inhibiting proliferation and inducing the differentiation of epidermal keratinocytes [ 14 ] stimulating proliferation of dermal fibroblasts and melanocytes [ 15 ], and production of proinflammatory cytokines [ 16 , 17 ]. Importantly, human peripheral tissues also express functional HPA equivalents, including CRH, adrenocorticotropic hormone, and cortisol, and provide negative feedback regulation [ 18 , 19 , 20 , 21 ]. This has been documented best in human skin, where CRH may exert a dual role: short-term pro-inflammatory actions (e.g., via the induction of mast cell (MC) degranulation) and longer lasting immunoinhibitory functions via the stimulation of local cortisol synthesis by keratinocytes [ 12 , 22 ].…”
Section: Introductionmentioning
confidence: 99%